2014
DOI: 10.46743/2160-3715/2010.1183
|View full text |Cite
|
Sign up to set email alerts
|

A Sex-Based Examination of Violence and Aggression Perceptions Among Adolescents: An Interactive Qualitative Analysis

Abstract: In this study I examine the critical factors and themes that are identified as salient influencers of overt and relational aggression among youth. Sex differences and similarities associated with such adolescent perceptions are assessed. Forty-eight ethnically diverse youth between the ages of 14 and 16 years participated in sex-specific focus groups and individual interviews. Sex-Specific Systems Influence Diagrams (SID), models of influences and outcomes, were created using the Interactive Qualitative Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…These findings offer a more specific focus on weapon violence compared to previous studies on antecedents of verbal and physical violence . Prior research indicates weapon violence among students is often triggered by peer-to-peer social interactions (Wyatt, 2010), whereas this study revealed that teachers are targets of weapon violence for different reasons and in different situations than student-centered violence. Their status as educators in the school ecosystem creates unique circumstances that may trigger violence.…”
Section: Situational Triggerscontrasting
confidence: 55%
See 1 more Smart Citation
“…These findings offer a more specific focus on weapon violence compared to previous studies on antecedents of verbal and physical violence . Prior research indicates weapon violence among students is often triggered by peer-to-peer social interactions (Wyatt, 2010), whereas this study revealed that teachers are targets of weapon violence for different reasons and in different situations than student-centered violence. Their status as educators in the school ecosystem creates unique circumstances that may trigger violence.…”
Section: Situational Triggerscontrasting
confidence: 55%
“…Research on situational triggers that lead to school weapon violence is limited. Available evidence suggests that bullying, verbal aggression, gang-related events, and physical fighting are influential triggers for weapon carrying and use between student peers (Wyatt, 2010). For violence against teachers, breaking up fights, disciplining students, or directing students to follow classroom and school rules have been identified as common antecedents of physical violence (i.e., physical attacks, objects thrown, weapon use; McMahon, Peist, et al, 2020).…”
Section: Proposed Theoretical Framework Of Weapon Violencementioning
confidence: 99%
“…Although the ideal group size for the IQA technique is 12-15 participants (Northcutt & Mccoy 2004;Wyatt 2010) 2019), it was decided to proceed with the smaller group. As a result of the small group size, additional interviewees were identified using snowball sampling to supplement the research findings and strengthen the data.…”
Section: Samplingmentioning
confidence: 99%
“…For instance, previous studies showed that trash talking is related to bullying, aggression, fighting and so forth (c.f. Wyatt, 2010;Rafferty & Vander Ven, 2014). 'Brand bullying' aims those who cannot afford the latest brands and fashions, which could potentially lead to exclusion by peers and bullying cases.…”
Section: Introductionmentioning
confidence: 99%